2023
DOI: 10.1002/jctb.7462
|View full text |Cite
|
Sign up to set email alerts
|

Development of an industrial sustainable process for wax esters production: enzyme immobilization, process optimization, and plant simulation

Abstract: BACKGROUND: As a result of the ban on whaling, there has been a shortage of spermaceti, a natural product with applications in cosmetics and pharmaceuticals. A green and sustainable process for the biocatalytic synthesis of a wax ester mixture analogue to natural spermaceti is presented in this paper.RESULTS: Immobilization of Candida antarctica lipase B by covalent binding to Purolite® Lifetech™ ECR8285 allowed for an immobilized derivative with 124.5 mg protein/g support (69.3% protein immobilization yield) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…PMI values for the overall cascade reaction and lipase-catalyzed esterification were found to be 21,746 and 2,038 kg/kg, respectively. When considering only reactants (i.e., fatty acids and fatty alcohols), the PMI of esterification was only 1.79, which was comparable to data reported for solvent-free reactions (PMI = 1.05) . This suggested that the resource-intensive step was the fatty alcohol production.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…PMI values for the overall cascade reaction and lipase-catalyzed esterification were found to be 21,746 and 2,038 kg/kg, respectively. When considering only reactants (i.e., fatty acids and fatty alcohols), the PMI of esterification was only 1.79, which was comparable to data reported for solvent-free reactions (PMI = 1.05) . This suggested that the resource-intensive step was the fatty alcohol production.…”
Section: Resultssupporting
confidence: 73%
“…When considering only reactants (i.e., fatty acids and fatty alcohols), the PMI of esterification was only 1.79, which was comparable to data reported for solvent-free reactions (PMI = 1.05). 21 This suggested that the resource-intensive step was the fatty alcohol production.…”
Section: Continuous Enzymatic Esterification and Processmentioning
confidence: 99%
“…To incorporate a greater number of studies, the search parameters were adjusted by removing the term “cosmetic”, resulting in 62 papers, of which 43 studies met the established criteria (tank reactors with a volume superior than 50 mL and cosmetic applications). Table 5 [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ] compiles these papers. The esters synthesized fall into these categories: emollient esters [ 60 , 61 , 62 , 65 , 69 , 70 , 71 , ...…”
Section: Reactors Used In the Biocatalytic Synthesis Of Esters With A...mentioning
confidence: 99%
“…Table 5 [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ] compiles these papers. The esters synthesized fall into these categories: emollient esters [ 60 , 61 , 62 , 65 , 69 , 70 , 71 , 73 , 74 , 79 , 80 ,…”
Section: Reactors Used In the Biocatalytic Synthesis Of Esters With A...unclassified
See 1 more Smart Citation